Effects of heat treatment on the structural, spectral, morphological, dielectric, and magnetic properties of Ba0.5Sr0.1Zn0.4Fe12O19 ferrite. Issue 17 (1st September 2021) - Shifa, Muhammad Shahzad; Khan, Waqar Ahmed; Albalawi, Hind; Al- Muhimeed, Tahani I.; AlObaid, Abeer A.; Mahmood, Q.; Khan, Muhammad Azhar; Gulbadan, Shagufta; Gilani, Zaheer Abbas; Qureshi, Imdadullah
Abstract: M-type Hexa-ferrites powders of chemical composition Ba0.5 Sr0.1 Zn0.4 Fe12 O19 was prepared by the use of the co-precipitation technique. The heat treatment of this ferrite composition was done at various temperatures (700, 800, 900, 1000, 1100, and 1200 °C) for 6 h. The X-ray diffraction (XRD) analysis of all the prepared powder samples confirmed the emergence of a hexagonal structure. The high-intensity peaks of the samples were indexed and showed a single phase. The size of crystallite was obtained within the range of 21–42 nm. The surface morphology was carried out with a Scanning electron microscope (SEM). The grain size showed the hexagonal shape, and average grain sizes were in the range of 211 nm. Spectral information was found using the Fourier transform infrared (FTIR) spectroscopy to confirm the phase of M-type hexaferrite. The dielectric parameters were measured within the high-frequency range of 5 MHz - 3 GHz. The dielectric constant was increased with an increase in temperature. The dielectric studies were found by the establishment of space charge polarization as per the two-layer model provided by Maxwell-Wagner and the study of phenomena of Koop's theory. The magnetic characteristics including coercivity (HcB) and retentivity (Br) were measured from BH/JH hysteresis loops. The enhancement of coercivity was observed from 1.23 × 10 +3 Oe to 1.50 × 10 +3 Oe, while the retentivity increased from 1.334 × 10 +3 G to 1.598 × 10 +3 G with an increase in temperature. Outstanding properties of synthesized materials suggested their use in large-frequency applications, including recording media and permanent magnets.